2021
DOI: 10.26464/epp2021020
|View full text |Cite
|
Sign up to set email alerts
|

A new inversion method for reconstruction of plasmaspheric He<sup>+</sup> density from EUV images

Abstract: Present a new method to reconstruct the plasmaspheric He + global density distribution from two dimensional Extreme Ultraviolet images. q The new method has superior performance with insufficient projection data. q The method can be generalized to study soft X-ray images from the Solar wind-Magnetosphere-Ionosphere Link Explorer mission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For more details of how this algorithm is implemented the reader is referred to Chambolle (2004), as well as to our earlier paper. In addition to the theoretical work by Huang Y et al (2021), which inspired the present work, tomographic reconstruction has also been applied to real space plasma observations, including those of Gustavsson (1998) and Aso et al (1998).…”
Section: Tomographic Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more details of how this algorithm is implemented the reader is referred to Chambolle (2004), as well as to our earlier paper. In addition to the theoretical work by Huang Y et al (2021), which inspired the present work, tomographic reconstruction has also been applied to real space plasma observations, including those of Gustavsson (1998) and Aso et al (1998).…”
Section: Tomographic Reconstructionmentioning
confidence: 99%
“…Our first step in analyzing soft X-ray emissions consisted of various fitting approaches to volume emissions or to boundaries determined in the images (Jorgensen et al, 2019;Sun TR et al, 2020. The next step, following the example of Huang Y et al (2021), was to investigate superposed epoch tomographic reconstruction of the magnetosheath using modeled observations from the Solar Wind Magnetosphere Ionosphere Link Explorer (SMILE) satellite (Wang C et al, 2017;Branduardi-Raymont et al, 2018). This work is detailed in Jorgensen et al (2022), and a summary can also be found in Wang C and Sun TR (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Tomographic techniques have previously been used in reconstructing the 3D shape of auroral formations (e.g., Aso et al., 1998; Gustavsson, 1998), and Huang et al. (2021) published an approach to reconstructing the plasmasphere from EUV images. The paper by Boone and McCollough (2021) discusses the history of medical tomography since it was initially developed 50 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are collectively referred to as tomographic techniques. Tomographic techniques have previously been used in reconstructing the 3D shape of auroral formations (e.g., Aso et al, 1998;Gustavsson, 1998), and Huang et al (2021) published an approach to reconstructing the plasmasphere from EUV images. The paper by Boone and McCollough (2021) discusses the history of medical tomography since it was initially developed In the following section, Section 2, we provide a brief general introduction to tomographic techniques, and then discuss how we apply them to imaging of X-ray emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The plasmasphere is composed of low-energy particles, forming a sphere-like reservoir of very cold (~1 eV), fairly dense plasma (~50−10 4 cm −3 ) that corotates with the Earth. Recently, the method for Extreme Ultraviolet (EUV) image reconstruction of the plasmasphere was improved by Huang Y et al (2021). The low-density region outside the plasmasphere is called the trough.…”
Section: Introductionmentioning
confidence: 99%